Carbon dots-based fluorescent films to act as a potential antioxidant agent and pH ratiometric sensor for skin applications - Da Silva, Livia E.; Araujo, Anna Paula de L.; Almeida, James Henrique; de Vasconcelos, Ledja. B. O. D.; Silva, Messias de O.; Lima, Dimas. J. P.; Viana, Rodrigo da S.; Ferro, Jamylle N. de S.; Goulart, Marília O. F.; Xavier, Jadriane A.; Barbosa, Cintya. D. A. E. S. (Frontiers in Carbon, 2023)
The wound healing process is accompanied by changes in pH values. Monitoring this physicochemical parameter can indicate the effectiveness of the applied treatment and act as early identification of wound infection. This study focuses on the development of a fluorescent film-based polyvinyl alcohol (PVA) and carbon dots (CDs) derived from lemon bagasse (CD-L) and ortho-phenylenediamine (CD-oPD) named to act as antioxidants and potential ratiometric fluorescent pH sensors, in wound applications. The I460/I550 intensity ratio, as a function of pH value for the dual-system CDs prepared from the mixture of CD-L and CD-oPD, named CD-L/oPD, was investigated. The fit corresponded to a sigmoidal function in the pH range of 5 to 10, with a relationship having a r2 = 0.992. The variation in the values of the I460/I550 ratio allows for the visualization of the color change from yellowish-green to green with increasing pH. Through a simulated ex vivo pig skin model, it was possible to note that the films prepared from mixed of the CD-L and CD-oPD carbon dots incorporated in a matrix PVA named CD-L/oPD-F was more efficient at visually discriminating color in relation to changes in pH than the films prepared from both individual CD-L (CD-L-F) and CD-oPD (CD-oPD-F) carbon dots. CD-L and CD-oPD demonstrated antioxidant capacity against reactive oxygen species (ROS). The IC50 values for CD-L and CD-oPD were 56.7 and 39.5 µg mL-1 in the DPPH● inhibition assay, and 25.1 and 63.4 µg mL-1 in the HOCl scavenging one, respectively. MTT viability assays using human non-tumoral skin fibroblast (HFF-1) cell showed a cell survival rate of over 80% for both CDs up to a concentration of 1000 µg mL-1. Finally, the developed films can act in a bifunctional way, by monitoring healing through pH changes and by acting as an antioxidant agent in the treatment of wounds.